GERAKAN DAKWAH SULTAN AGUNG (Arti Penting Perubahan Gelar Sultan Agung Terhadap Gerakan Dakwah di Jawa Pada Tahun 1613 M - 1645 M) - Hariyanto Hariyanto (Jurnal Al-Bayan: Media Kajian dan Pengembangan Ilmu Dakwah, 2018)
The peak of the glory of the Mataram kingdom occurred during the reign of Sultan Agung. He managed to perform da'wah movement to master Central Java, East Java and some areas in West Java. Many strategies of da'wah movement conducted by Sultan Agung. However, the change and the addition of the title by Sultan Agung is one thing that distinguishes the previous Mataram kings. Sultan Agung recorded the changes and the addition of his title ranging from "Panembahan" to "Susuhunan" or "Sunan", to "Sultan" Degree "Susuhunan" or "Sunan" commonly used by the guardian gives charisma (authority) to the king. The title is used karen areas that have mastered the territory of the great Muslim Guardians. The title of "Sultan" which bears Sultan Agung further strengthens himself as a leader as well as a figure of Religion, who has responsibility towards his people and its creator . Complexity of the title that carried the Sultan Agung able to raise its degree and bring social effects for the movement of his da'wah. Areas that did not initially recognize themselves as kings, managed to recognize themselves as kings and submit and obey the king's policies. The complete title of Sultan Agung known as "Sultan Agung Hanyakrakusuma Senapati Ing Alaga Sayyidin Panatagama Khalifatullah" has the meaning that the third Mataram King is a leader who gets the mandate from Allah to organize the life of his people. Keywords: Title, Sultan Agung, Movement of Da'wah